Cold Pressor Test as a Potential Early Screening Tool for Identifying Young Adults at Risk of Developing Hypertension - Dandi Oka Subantara; Yeli Yulianti (FORIKES, 2026)
Hypertension remains a major public health concern in Indonesia, with a steadily increasing prevalence across age groups, including young adults. Individuals with a family history of hypertension are at heightened risk due to genetic predisposition and lifestyle factors, making early detection of cardiovascular reactivity essential. The cold pressor test is a well‑established physiological stress test used to assess sympathetic activation and acute blood pressure responses. This study aimed to examine the effect of the cold pressor test on systolic and diastolic blood pressure among young adults with a hereditary history of hypertension in Tasikmalaya, West Java. A quasi‑experimental quantitative design with a single‑group pre‑test and post‑test structure was employed. The study was conducted over three months at Universitas Bakti Tunas Husada and involved 178 respondents selected through consecutive sampling based on predefined inclusion and exclusion criteria. Blood pressure was measured before and after cold pressor test using a calibrated digital sphygmomanometer, and data were analyzed using descriptive statistics and paired t‑tests. The findings demonstrated a significant increase in both systolic and diastolic blood pressure following cold pressor test exposure. Mean systolic pressure rose from 118.80 mmHg to 137.22 mmHg, while mean diastolic pressure increased from 77.70 mmHg to 82.95 mmHg. Both changes were statistically significant (p < 0.05), indicating heightened cardiovascular reactivity among individuals with a family history of hypertension. These results suggest that cold pressor test may serve as a useful early screening tool for identifying young adults at risk of developing hypertension, thereby supporting timely preventive interventions.Keywords: hypertension; cold pressor test; blood pressure reactivity; young adults; family history of hypertension